Looking at-- Hypsilophodon : a dinosaur from the Cretaceous period - Coleman, Graham, frey50; Gibbons, Tony (Milwaukee : Gareth Stevens Pub., 1997)
Describes the physical characteristics and probable behavior of this two-legged plant-eating dinosaur built for speed.
Includes index.
Keywords: Hypsilophodon -- Juvenile literature; Hypsilophodon; Dinosaurs